Hubungan Antara Dukungan Keluarga Dengan Kecenderungan Perilaku Delinkuen Pada Remaja - Kartika Sari, Novi; Sri Hertinjung, Wisnu Sri Hertinjung., S.Psi, M.Psi, Psi (2016)
Delinkuen behavior is behavior that deviates from the norm rules that are usually committed by juveniles . One of the factors that influence this behavior is family support .This study aims to determine the relationship between family support delinkuen behavioral tendencies in adolescents, to determine the level of support the family, to determine the level of delinkuen behavioral tendencies and to determine the effective contribution of family support for behavioral tendency delinkuen. Researchers used quantitative methods to achieve the objectives of this research. Subjects used in this study were students of class IX Junior High School (SMP) Negeri 2 Sawit, Boyolali. The results of the correlation coefficient (r) of -0.707 with sig. (One-tailed) = 0,000; p <0.01 indicates no significant negative relationship between family support delinkuen behavioral tendencies in adolescents. Based on the results of analysis variables delinkuen behavioral tendencies have the empirical mean (RE) of 81.71 and the mean hypothetical (RH) of 112.5 means delinkuen behavioral tendencies of research subjects is low. Variable support the family has the empirical mean (RE) amounted to 111.30 and the mean hypothetical (RH) of 90 which means the family support the research subjects is high. The effective contribution of family support 49.98% against delinkuen behavioral tendencies in adolescents. Keywords: delinkuen behavioral tendencies, family support, adolescents.